Comparative Efficacy of Nebulized 7% Hypertonic Saline versus 0.9% Normal Saline with Salbutamol in Children with Acute Bronchiolitis - Islam, Md Saiful; Mollah, Md Abid Hossain; Khanam, Rokeya; Chowdhury, Abu Sayeed; Rahman, Md Mahfuzur; Baqui, Shah Abdullah Al; Rashid, Muhammed Anisur (Bangladesh Journal of Child Health, 2019)
Background: Acute bronchiolitis is an acute viral lower respiratory tract infection of infants and is the leading cause of hospitalization of infants below 2 years of age. Being a viral disease, there is no effective treatment of this problem other than supportive care. To provide this care, both 0.9% normal saline with salbutamol and 3% hypertonic saline has been found effective. This study was undertaken to assess the efficacy of 7% hypertonic saline on recovery from acute bronchiolitis. Methodology: This was a randomized controlled trial, carried out in the Department of Paediatrics, Dhaka Medical College Hospital (DMCH), Bangladesh between January 2015 to December 2015. A total of 90 children from 1 month to 2 years of age of either sex who were diagnosed and admitted as acute bronchiolitis were enrolled. After enrollment, they were randomly assigned to either 7% nebulized hypertonic saline (Group-I = 45) or to 0.9% nebulized normal saline with salbutamol (Group-II = 45). The efficacy was determined by assessing clinical severity score and length of hospital stay. Data were analyzed using computer software SPSS version 19. Result: In this study the two groups were almost similar with respect to their demographic and baseline clinical severity score. After intervention the clinical severity score of both treatment modalities were reduced (Group-I(HS) were 7.9, 6.8, 3.8, 1.4, 1.33 while in Group-II(NS+ Salbutamol) score were 8.6, 7.6, 4.9, 3.11, 2.12) but the reduction was significant more in children who received 7% nebulized hypertonic saline than those who received 0.9% nebulized normal saline with salbutamol. Majority 42(93.3%) of group-I(HS) children recovered at the end of 72 hours whereas 17(37.8%) of the children of group-II (NS+ Salbutamol) recovered from the disease during the same period. Length of hospital stay was shorter in hypertonic saline group compared to normal saline with salbutamol group (56.36±12.33 hours vs71.07±13.48 hours, p<.001). The patients of hypertonic saline group required a shorter duration of oxygen therapy compared to normal saline with salbutamol group (12.53±3.58) hours vs (20.25± 4.15) hours, (p=0.009). Conclusion: 7% hypertonic saline was found more effective than 0.9% normal saline with salbutamol in terms of reducing clinical severity, length of hospital stays and duration of oxygen therapy. Bangladesh J Child Health 2019; VOL 43 (2) :80-84